Effects of educational unification - Qassem Abdazzarhra Hasab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Man believes in the existence of unseen power, and he needs it due to his weakness, poverty and nature but his ignorance and his distance from the righteous parents of God prevents him from knowing the truth and reaching it. But with education and upbringing and accompanying the righteous parents of God It makes it easier for him to get closer to knowledge. With this luminous knowledge, man becomes one of the monotheists, after it is fulfilled, He has the reality of monotheism in its true forms. That is, God Almighty is the One, He has no partner. And that God Almighty exists, real, spiritual, simple, devoid of all kinds of structure he has no part nor he is part of anything in order for this monotheism to be effective in human existence, it must be rationally established by evidence the consolidation of this important pillar (monotheism) in human belief leads to many educational effects on his individual and social life Including: self-awareness servitude, supplication, trust, unity and union with the order of existence, in addition to hope, tranquility, patience, and freedom.